Tinjauan Hukum Penerapan Green Industry Era 4.0: Implementasi Biomassa Ramah Lingkungan Melalui Limbah Sawit Berbasis Sustainable Development - Hayfa, Jessenia; Risqiana; Berlian , Daffa Aditra Bintang (JAMI: Jurnal Ahli Muda Indonesia, 2024)
Backgrounds. This research aims to identify challenges and obstacles in using energy biomass from palm oil waste in Indonesia, as well as to analyze regulations related to the implementation of green industry era 4.0 in the context of biomass use. Apart from that, the text also highlights the importance of effective natural resource management in accordance with Article 33 paragraph (3) of the 1945 Constitution, as well as discussing the potential of palm oil waste as an environmentally friendly renewable energy source. Methods. This research uses a normative juridical approach to assess the legal framework that supports green industry, especially in using palm oil waste for sustainable development. Data was obtained from a literature study of primary, secondary and tertiary legal norms. The aim of the research is to describe and analyze regulations and obstacles in implementing biomass in the green industry era 4.0 in Indonesia. Results. Regulations in Indonesia related to the implementation of green industry era 4.0 in the sustainable use of biomass from palm oil waste are regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. This regulation integrates environmental, social and economic dimensions in development strategies to achieve environmental sustainability, community welfare and a good quality of life. The main challenges in implementing green industry include inadequate infrastructure and technology, economic and policy challenges, social problems, and limited availability of human resources. The proposed strategy includes the use of technology 4.0, biorefinery development, increasing public awareness, strengthening regulations, and multi-stakeholder collaboration. Conclusions. The Indonesian government has developed sustainable industrial development by applying green industry principles, especially in the use of biomass from palm oil waste as renewable energy. However, challenges such as climate change and inadequate infrastructure still need to be addressed. It is hoped that with a strategy to overcome this, Indonesia can optimally utilize biomass energy while maintaining environmental sustainability.